Nanotribology and Nanomechanics An Introduction - Bhushan, Bharat; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This textbook and comprehensive reference source and serves as a timely, practical introduction to the principles of nanotribology and nanomechanics. This 4th edition has been completely revised and updated, concentrating on the key measurement techniques, their applications, and theoretical modeling of interfaces. It provides condensed knowledge of the field from the mechanics and materials science perspectives to graduate students, research workers, and practicing engineers.
Introduction - Measurement Techniques and Applications -- Part I. Scanning Probe Microscopy: Scanning Probe Microscopy - Principle of Operation, Instrumentation and Probes -- Calibration of Normal and Lateral Forces in Cantilevers used in Atomic Force Microscopy -- Biomedical Sensing with the Atomic Force Microscope -- Part II. Nanomechanics: Nanomechanical Properties of Solid Surfaces and Thin Films -- Nanomechanical Properties of Nanostructures and Scale Effects -- Computer Simulations of Nanometer-Scale Indentation and Friction -- Part III. Nanotribology: Nanotribology, Nanomechanics, and Materials Characterization Studies Using Scanning Probe Microscopy -- Surface Forces and Nanorheology of Molecularly Thin Films -- Atomic Scale Friction Phenomena -- Scale Effect in Mechanical Properties and Tribology -- Part IV. Molecularly-Thick Films for Lubrication: Nanotribology of Ultrathin and Hard Amorphous Carbon Films -- Self-Assembled Monolayers for Controlling Adhesion, Friction, and Wear.-Nanoscale Boundary Lubrication Studies -- Part V. Industrial Applications: Micro/Nanotribology and Micro/Nanomechanics of Magnetic Storage Devices -- Nanotribology and Nanomechanics of MEMS/NEMS and BioMEMS/NEMS Materials and Devices.
Keywords: Microtechnology; Microelectromechanical systems; Nanotechnology; Nanoscience; Coatings; Tribology; Corrosion and anti-corrosives.; Microsystems and MEMS; Nanotechnology; Nanophysics; Coatings; Tribology; Corrosion